1991
DOI: 10.1128/jb.173.7.2301-2310.1991
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulatory loci coupling flagellin synthesis to flagellar assembly in Salmonella typhimurium

Abstract: The complex regulation of flagellin gene expression in Salmonella typhimurium was characterized in vivo by using lac transcriptional fusions to the two flagellin structural genes (fliC [Hl] andfljB [H2]). Phase variation was measured as the rate of switching of flagellin gene expression. Switching frequencies varied from 1/500 per cell per generation to 1/10,000 per cell per generation depending on the particular insertion and the direction of switching. There is a 4-to 20-fold bias in favor of switching from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
144
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(147 citation statements)
references
References 58 publications
(33 reference statements)
2
144
0
Order By: Relevance
“…To test the relevance of bacterial motility in conditions of host cell stress, we used the Salmonella motility‐deficient mutant strain Δ fliC , which lacks the fliC gene but retains expression of FljB. However, the frequency of flagellin switching is low [approximately 1/5,000 per cell per generation, biased toward the fljB OFF orientation (Gillen & Hughes, 1991)], and thus, the Salmonella Δ fliC mutant strain is essentially non‐motile. Additionally, we used a completely non‐motile Salmonella mutant (Δ flhC ), due to an insertion of the MudJ transposon into the flagella master regulator flhC gene.…”
Section: Resultsmentioning
confidence: 99%
“…To test the relevance of bacterial motility in conditions of host cell stress, we used the Salmonella motility‐deficient mutant strain Δ fliC , which lacks the fliC gene but retains expression of FljB. However, the frequency of flagellin switching is low [approximately 1/5,000 per cell per generation, biased toward the fljB OFF orientation (Gillen & Hughes, 1991)], and thus, the Salmonella Δ fliC mutant strain is essentially non‐motile. Additionally, we used a completely non‐motile Salmonella mutant (Δ flhC ), due to an insertion of the MudJ transposon into the flagella master regulator flhC gene.…”
Section: Resultsmentioning
confidence: 99%
“…In the enteric bacteria an intact hook-basal body complex must be assembled before flagellin is expressed (21,36), and genetic studies have demonstrated a hierarchy of flagellar assembly, motility, and chemotaxis gene expression responsible for this structural regulation (13,14,22,23). A negative regulator of flagellin expression, designated FlgM, that is responsible for the coupling of hook-basal body assembly to flagellin expression has been identified in S. typhimurium (13,14).…”
Section: Resultsmentioning
confidence: 99%
“…The cF factor of E. coli displays a promoter specificity similar to that of aD and has been shown to transcribe certain flagellar and chemotaxis genes in that organism (3). The gene for the uF factor was identified in S. typhimurium as being thefliA locus (32), part of a class of fla, che, and mot genes termed class II genes (13,14,22,23).…”
mentioning
confidence: 99%
See 2 more Smart Citations